Pengaruh Bimbingan Karier Terhadap Perencanaan Karier Siswa Jurusan TKJ Kelas XI di SMK Mandiri Datuk Kabu Deli Serdang - Addini Putri Devani; Saiful Akhyar Lubis; Abdul Aziz Rusman (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Career guidance helps individuals choose, prepare, and plan their chosen career for the future.  This research aims to determine the description of students' career planning in class XI TKJ Mandiri Vocational School Datuk Kabu Deli Serdang and the influence of career guidance on students' career planning.  This research is a type of quantitative research.  The design of this research is Pre-Experimental Designs in the form of One Group pretest-posttest Design.  A questionnaire with a Likert scale was used to collect data.  The results of the research show that the career planning of students majoring in Class XI TKJ at SMK Mandiri Datuk Kabu Deli Serdang is influenced by career guidance.  The results of data analysis carried out using the IBM SPSS Statistics V.26 program show that the Sig.  (2-tailed) is 0.000.  If 0.000<0.05 then, Ho is rejected and Ha is accepted.  Thus, it was found that there was an influence on students' career planning both before and after being given career guidance.